COVID-19 research trends in the fields of economics and business in the Scopus database in November 2020 - Handoko, Luqman Hakim (Science editing, 2021)
Purpose: This study explored the state of the literature on coronavirus disease 2019 (COVID-19) in two subject areas: (1) economics, econometrics, and finance, and (2) business, management, and accounting. The study focused on the most productive and influential journals, countries, institutions, documents, and clusters of keywords.Methods: Data were retrieved from Scopus on November 21, 2020. The search term was the keyword “COVID-19” in the title, abstract, and author’s keywords, and the articles were limited to two subject areas. The data were analyzed using VOSviewer and Excel.Results: In the analysis of 1,719 articles on COVID-19, the most productive journal that published these articles was Gender, Work, and Organization (n=49). The most productive country and institutions were the United States (n=526) and Universiteit van Pretoria (n=16) and the University of Oxford (n=16), respectively. Based on citations, the most influential authors, countries, and journals were Dmitry Ivanov (n=233), the United States (n=1,027), and Finance Research Letters (n=326), respectively. The most cited article was authored by Stefan Gossling (n=157) on the impact of COVID-19 on society, the economy, and tourism. The articles were from 111 countries, of which 85.6% had collaborations. The keywords of research on COVID-19 formed 14 clusters (e.g., small and medium enterprises, aviation, tourism, banking and finance, supply chain, economic growth, and the digital economy).Conclusion: The number of COVID-19 articles related to economics and business is fairly large and is continuing to grow significantly. The keyword analysis showed that COVID-19 has had a tremendous impact on all economic sectors.